F192. Role of multimodal extra and intraoperative Stereoelectroencephalography (sEEG) monitoring in tailoring staged surgical resection in patients with eloquent cortex (Rolandic) pharmacoresistant epilepsy. (May 2018) - Aung, Thandar; Maldonado, Andres; Bulacio, Juan; Wang, Irene; Prayson, Richard; Wyllie, Elaine; Najm, Imad; Gonzalez-Martinez, Jorge
Abstract : Introduction: To describe the feasibility, safety and seizure outcome of patients with medically intractable rolandic epilepsy(RE) who underwent staged resections guided by multimodal extra and intraoperative SEEG recordings. Methods: We retrospectively studied and analyzed patients, who underwent extra and intraoperative intracranial invasive stereoEEG monitoring, data related to semiology, non-invasive electrophysiology, imaging, type of resection, complications, surgical pathology results and seizure outcome from January 2015 through September 2017, under Cleveland Clinic IRB. Results: Five patients were identified as having intractable RE based on analysis of pre-surgical evaluation using 3T magnetic resonance imaging (MRI), magnetoencephalography(MEG) and positron emission tomography (PET). Preoperative magnetic resonance imaging were considered nonlesional in all five patients but after the pre-surgical evaluation, there were abnormal sulcation pattern or increased signal in white matter were noticed which are of unknown significance. All five patients were underwent sEEG implantation with hypothesis of peri-rolandic or paracentral lobule regions being epileptogenic. Extra-operative sEEG data in all patients showed ictal onset zone involving rolandic cortex (hand knob and paracentral lobule), premotor and/or supplementary motor area (SMA). In two patients, hand knob rolandic cortex was the region of interest The other three being paracentral lobule (leg motor). Given all the data (semiology, sEEG data and pre-sugical evaluation), the conclusion of epileptogenic zone (EZ) being close proximity to eloquent cortex. Given the semiology, staged resection approach with continuous sEEG recording was performed in the operating room. Resection of interictally active non-eloquent cortex electrodes was performed first guided by real-time intraoperative sEEG (electrophysiology) data. The resection was also guided by the sEEG electrode in three dimensions. Resolution of rolandic hand motor spike activities was documented after resection of SMA in three patients, cingulate and pre-motor areas in one patient. In the last patient, hand sensory area was resected sparing motor cortex. Three out of five patients did not have any deficit but two had mild foot drop. Pathology showed focal cortical dysplasia type (IB, IIA, and IIB) and a possible vascular malformation in another. All patients were reported to be seizure free at follow up period of 6–28 months. Conclusion: Taken into account of hyper-synchronous connectivity in frontal and parietal rolandic regions, we present a case series of patients who underwent staged resections guided by a novel multimodal method of invasive monitoring. The results of this highly selected group of patients testify for the feasibility and safety of a novel multimodal method of invasive monitoring, combining the benefits of both intra and extra-operative SEEG recording, especially operating around the central lobule near hand knob regions.